Plural Money, Socially-Provided Goods, and the Principal-Agent Problem - Prewitt, Matt; Weyl, E. Glen (RadicalxChange, 2022)
Money is an economic lubricant: it helps goods and services slip and slide toward where they can be used more efficiently. Without lubricant, things get “stuck”. They don’t go where they’re needed most, and value is wasted. Yet, sometimes using money backfires, causing goods to be distributed less efficiently. Consider public education. Giving citizens cash, instead of schools, would less efficiently achieve the important public objective of education. Individuals might, for example, misspend the money, or fail to coordinate around supporting efficient, broadly shared institutions. The same logic holds for roads, telecommunications, and other socially-provided goods that support broadly shared goals.